The Extent of Imam al-Bukhari's Influence on the Iraqi School of Hadith and his Influence on it: Analytical and Critical Study - Haifa M. Al-Ziadah; Najah M. Al-Azzam (دراسات: علوم الشريعة والقانون, 2022)
Objectives: To show the extent to which Imam Al-Bukhari influenced and influenced by the Iraqi School of Hadith, by exploring his scientific trips to the main cities and metropolises of Iraq. Another objective is to mention the most prominent Iraqi sheikhs and their impact on shaping Al-Bukhari’s Hadith personality, and to show the most prominent of his students who learned from him in this pioneering school and its impact on the formulation and refinement of their scientific personalities.